Effect of soaking and sprouting on protein content and transaminase activity in pulses - Dipnaik, Kavita; Bathere, Deepika (International Journal of Research in Medical Sciences, 2017)
Background: Pulses belong to the family leguminosae. Pulses provide protein and fibre, as well as vitamins and minerals, such as iron, zinc, folate, and magnesium. In addition, the phytochemicals, saponins, and tannins found in pulses possess antioxidant and anti-carcinogenic effects, indicating that pulses may have significant anti-cancer effects. It is the practice of germinating seeds to be eaten raw or cooked. Sprouts can be germinated at home or produced industrially. The metabolic activity of resting seeds increases as soon as they are hydrated during soaking. Sprouting grains causes increased activities of hydrolytic enzymes like lipase, improvements in the contents of total proteins, fat, essential amino acids, total sugars, B-group vitamins and starch digestibility, and decrease in phytates and protease inhibitors an increase in amino acid lysine is seen after sprouting, increase in proteolytic activity leads to hydrolysis of prolamins and increased lysine. Methods: Proteins and transaminase activity were estimated from Green mung (Vignaradiata), Cowpea (Vignaunguiculata), Chick pea (Cicerarietinum), Moth bean (Vignaaconitifolia) and Black gram (Vignamungo) in raw (dried) state, after soaking for 12 hours and on sprouting. Students paired t-test was applied to data and statistical significance was established. Results: Chick pea showed highest concentration of proteins whereas Black gram showed the least protein content. Concentration of protein after 12 hours of soaking resulted in chick pea showing highest concentration of proteins whereas green gram showed the least protein content. Chick pea was superior amongst the pulses, because it showed highest protein content after sprouting and highest alanine transaminase activity in 12 hours soaked sample as well as in sprouted sample. Raw moth bean showed highest alanine transaminase activity. Conclusions: Protein content and transaminase activity were found to be highest in sprouted pulses. So, consumption of sprouted pulses should be encouraged. Amongst the pulses studied chickpea (Cicerarietinum) gave the maximum nutritional benefit because of its high protein content and high alanine transaminase activity, as compared to other (green gram, cowpea, moth bean and black gram) pulses.